Are Women Really Less Competitive Than Men? Career Duration in Nordic and Alpine Skiing - Frick, Bernd; Moser, Katharina (Frontiers in Sociology, 2021)
Do women shy away from competition while men compete too much? The available, mostly experimental evidence generally supports these assumptions. However, in contrast to laboratory settings, labor markets do not have random assignment of workers. Instead, individuals – professional athletes and corporate executives – self-select into specific occupations. Using data from Alpine and Nordic skiing over 52 and 37 years respectively, we show that career length of men and women is virtually identical. Thus, when adequately controlling for self-selection into a highly competitive environment, differences between men and women with respect to competitiveness com-pletely disappear.